Asuhan Kebidanan pada Ny. D Umur 33 Tahun G2P1A0 di PMB Nur Laila - Nur Laila; Yulia Nur Khayati (Universitas Ngudi Waluyo, 2025)
The role of midwives is very important in reducing maternal and child mortality rates through continuous midwifery care from preconception, pregnancy, childbirth, postpartum, to family planning, in accordance with midwifery standards that can be carried out independently, collaboratively, or through referrals. The descriptive research method and type of descriptive research used are case studies with documentation using the SOAP method. The case study was conducted on Mrs. D aged 33 years in November 2024 to March 2025 with data collection methods using observation, interviews and document studies. Midwifery care began from the third trimester pregnancy visit, the mother complained of frequent urination and difficulty sleeping at night. The efforts made were education about the discomfort she experienced was normal. Delivery was carried out spontaneously without complications at Puri Asih Hospital, Salatiga at 39 weeks of gestation. The baby's birth weight was within normal limits and no congenital abnormalities were found. Postpartum care was carried out 4 times and no gaps were found. Family Planning Services The mother chose to use 3-month injections. Continuity of Care (COC) or continuous midwifery care for Mrs. D can be carried out and is well received by the mother, husband and other family members. The mother and family feel the benefits so that the mother and family's knowledge increases. Abstrak Peran bidan sangat penting dalam menurunkan AKI dan AKB melalui asuhan kebidanan berkesinambungan